Insomniac children maternal sleep and mood in São Paulo and Barcelona Sono e humor de mães de crianças pequenas com insônia em São Paulo e Barcelona - Eduardina Tenenbojm; Angelis Geisa; Sueli Rossin; Eduard Estivill; Francisco Segarra; Rubens Reimão (Arquivos de Neuro-Psiquiatria)
OBJECTIVE: To evaluate sleep characteristics verifying for the presence of depressive symptoms in mothers of insomniac children living in São Paulo (Brazil) and Barcelona (Spain). METHOD: Forty-six mothers were evaluated, 37 from São Paulo and nine from Barcelona, their ages varying from 19 to 44, and their children; otherwise healthy but with complaints of insomnia, their age varying from three to 33 months. The mothers' sleep quality was rated by the Pittsburgh Sleep Quality Index (PSQI), and the Beck Depression Inventory (BDI). RESULTS: 91.30% of mothers reported poor sleep by PSQI standards. Regarding signs and symptoms of depression, 69.56% of all mothers in this sample showed them. Direct correlation between São Paulo mothers PSQI and BDI was found and also between the child's age and BDI. CONCLUSION: The mothers' poor sleep was related to mood changes with symptoms of depression presenting similar results in both cities. OBJETIVO: Avaliar a presença de sintomas depressivos em mães de crianças com insônia em São Paulo e Barcelona. MÉTODO: Quarenta e seis mães foram avaliadas, 37 de São Paulo e nove de Barcelona, suas idades variaram de 19 a 44 anos, e suas crianças, saudáveis, mas com queixa de insônia tinham idades de três a 33 meses. A mãe foi avaliada pelo Índice de Qualidade de Sono de Pittsburgh (PSQI) e pelo Índice de Depressão de Beck (IDB). RESULTADOS: 91,30% das mães relataram sono ruim pelo padrão do PSQI. Quanto aos sinais e sintomas de depressão, 69,56% das mães da amostra total relatavam. Nas mães de São Paulo foi constatada correlação direta entre o PSQI e o IDB, bem como a idade da criança e o IBD. CONCLUSÃO: O sono ruim das mães se correlacionou com sinais e sintomas depressivos e os resultados foram semelhantes nas duas cidades.